2017
DOI: 10.1111/fcsr.12218
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Predictors of Parenting Educators’ Technology Acceptance Attitudes

Abstract: The purpose of this study was to examine technology use by licensed parenting educators and to explore workplace conditions as influences on the educators’ technology acceptance attitudes. The study adapted the Technology Acceptance Model (TAM) as a theoretical framework and proposed 10 hypotheses to be examined. Responses to an online survey (N = 279) indicated that information search and email were used most frequently. In contrast, social media and online learning platforms were infrequently used. Structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 35 publications
2
8
0
2
Order By: Relevance
“…Sometimes they use social media, and they are least often (if at all) using more novel applications like Second Life (virtual reality). These results mimic those from the author's research with a smaller national sample of family educators in 2010 [42] and with state specific parenting educators in 2013 [31,40]. Yet it also reflects observations about other educator groups who, depending on the availability of resources, will default to technologies that are familiar and likely used in their personal lives [37,48].…”
Section: Family Educators' Technology Use: 'It Depends'supporting
confidence: 73%
See 3 more Smart Citations
“…Sometimes they use social media, and they are least often (if at all) using more novel applications like Second Life (virtual reality). These results mimic those from the author's research with a smaller national sample of family educators in 2010 [42] and with state specific parenting educators in 2013 [31,40]. Yet it also reflects observations about other educator groups who, depending on the availability of resources, will default to technologies that are familiar and likely used in their personal lives [37,48].…”
Section: Family Educators' Technology Use: 'It Depends'supporting
confidence: 73%
“…For the current study, the hypotheses are driven by anticipated differences in the contexts of family educators by type. Previous study of parenting educators (e.g., [40,41]) and of family life educators [22] reveal that those who work predominantly as family educators work with adult audiences, and in community-based programs. Those who work more occasionally in family education represent a wider range of work settings and audiences and their occasional educator status would seem to motivate their use of technologies for education differently.…”
Section: Motivations and Influences On Usementioning
confidence: 99%
See 2 more Smart Citations
“…daily communication-routines leads to the effect, that the visible artefact ESN becomes an 'invisible' but constantly available infrastructure, if it does not require high cognitive efforts to use it in daily work routines (front-end, interface) and if it runs smoothly without interruptions (back-end, server). Walker and Hong (2017) demonstrated that the presence of workplace infrastructure is related to users' perceived usefulness. Similar effects have already been shown in the context of e-learning technology, in which Wedel and Rothlauf (2014) demonstrated the mediated influence of infrastructure availability on perceived usefulness.…”
Section: Utilitarian and Hedonic Motivation For Using Esnsmentioning
confidence: 99%